2005
DOI: 10.1029/2005tc001796
|View full text |Cite
|
Sign up to set email alerts
|

Central Tanzanian tectonic map: A step forward to decipher Proterozoic structural events in the East African Orogen

Abstract: On the basis of a compilation of geological maps from central Tanzania coupled with structural and petrological studies a distinction is made between the tectonic evolution of the 1.8–2.0 Ga Usagaran orogeny and the 650–580 Ma Pan‐African orogeny in the Mozambique Belt. The geometry of both orogens is determined by displacement partitioning around the indenting Tanzania Craton. The Usagaran Belt formed by strike‐slip tectonics in an island arc regime. By contrast, the Mozambique Belt formed by westward thrust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…9). They are also consistent with reported igneous and metamorphic ages from the southern klippen (Krö ner et al 1997;Grantham et al 2008), suggesting that they are remnants of the same granulite-facies nappe complex that may have continued northward into the Eastern Granulites in Tanzania (e.g., Coolen et al 1982;Fritz et al 2005) and southward (within a reconstructed Gondwana) into the Schirmacher Oasis in East Antarctica (Baba et al 2010). A group of younger (!490 Ma) U-Pb and 40 Ar/ 39 Ar ages in the CDNC is not well understood and may indicate limited reactivation of collisional structures, for example, during extension.…”
Section: Regional Implications and Discussionsupporting
confidence: 85%
“…9). They are also consistent with reported igneous and metamorphic ages from the southern klippen (Krö ner et al 1997;Grantham et al 2008), suggesting that they are remnants of the same granulite-facies nappe complex that may have continued northward into the Eastern Granulites in Tanzania (e.g., Coolen et al 1982;Fritz et al 2005) and southward (within a reconstructed Gondwana) into the Schirmacher Oasis in East Antarctica (Baba et al 2010). A group of younger (!490 Ma) U-Pb and 40 Ar/ 39 Ar ages in the CDNC is not well understood and may indicate limited reactivation of collisional structures, for example, during extension.…”
Section: Regional Implications and Discussionsupporting
confidence: 85%
“…The eastern parts of the Usagaran Belt were reworked during the Neoproterozoic East African Orogeny and have been designated the Western Granulites, while further to the east, a unit of younger Mesoproterozoic rocks composed of enderbitic gneisses (metamorphosed igneous rocks of the charnockite series), schists, and marbles has been named the Eastern Granulites (Fritz et al, 2005). The Eastern and Western Granulites were metamorphosed simultaneously, and together they constitute the Neoproterozoic Mozambique Belt of Tanzania and Kenya.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Structurally, the Usagaran Belt constitutes the eastern border of the Archean Tanzania Craton (see, e.g., Fritz et al, 2005).…”
Section: Geologic Settingmentioning
confidence: 99%
“…These rocks, known broadly as the "Western Granulites" (e.g. Fritz et al, 2005) were first shown to have Neoarchaean protolith ages by Maboko (2000). Direct U-Pb zircon dating at ca.…”
Section: Precambrian Geology Of the Studied Areasmentioning
confidence: 99%